The Effect of Massage Effleurage on the Back and Breasts on Milk Production in Postpartum Mothers in the Working Area of the Barong Tongkok Health Center in 2022 - Diah Puspita Ulan; Endah Wahyutri; Nursari Abdul Syukur (Formosa Journal of Science and Technology, 2023)
This study aims to analyze the effect of massage effleurage on the back and breasts on milk production in postpartum mothers. This type of research is a quantitative research with a quasi-experimental research design by way of a pre-post test. The population in this study were all postpartum mothers who live in the working area of ​​the Barong Tongkok Health Center, totaling 50 people. Data collection was carried out directly using questionnaires and observation sheets. Data analysis techniques used the Wilcoxon mean difference test for each group and the Mann Whitney test for differences in post test results between the two groups. Based on the research results obtained, it can be concluded that there is an effect of massage effleurage on milk production in postpartum mothers in the working area of ​​the Barong Tongkok Health Center in 2022 with a p-value ¬= 0.000 (<0.05).